2021
DOI: 10.1515/ijamh-2021-0058
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between obesity, gestational diabetes mellitus, and pregnancy outcomes: an overview

Abstract: Obesity has been identified mainly as a raise in the body’s adiposity leading to prolonged overshoot of caloric intake over expenditure. Obesity has significant health-altering implications which have been shown to be implicated in the pathogenesis and progression of other diseases through its extensive physiological assaults. The prevalence of overweight and obesity has been an increasing epidemic worldwide. The number of obese births was even on the increase, with an increasing number of women of reproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…And univariate logistic regression analysis also confirmed that BMI in early pregnancy was a risk factor for GDM (Table 3 ). Our results support the previous view that overweight and obesity significantly increase the risk of GDM [ 48 , 49 ]. Women who develop GDM often have a subclinical metabolic dysfunction before pregnancy compared with women without GDM.…”
Section: Discussionsupporting
confidence: 92%
“…And univariate logistic regression analysis also confirmed that BMI in early pregnancy was a risk factor for GDM (Table 3 ). Our results support the previous view that overweight and obesity significantly increase the risk of GDM [ 48 , 49 ]. Women who develop GDM often have a subclinical metabolic dysfunction before pregnancy compared with women without GDM.…”
Section: Discussionsupporting
confidence: 92%
“…Obesity is the main influencing factor of PE in women with GDM in this paper. There are many of same pathophysiological changes between obesity and GDM, but obesity was concluded to be associated with greater oxidative stress and inflammation including the imbalance of fat factors ( 181 ), which are related to the occurrence of PE. Hyperinsulinemia and insulin resistance caused by obesity before pregnancy are related to the migration of cytotrophoblast and the reduction of uterine spiral artery remodeling, which is more likely to lead to placental ischemia ( 182 ).…”
Section: Mechanism and Predictive Markersmentioning
confidence: 99%
“…Obesity and excessive weigh gain are common conditions that increase GDM development risk [ 300 ]. Obesity per se is related to increased risk of pregnancy-induced hypertension, preeclampsia, risk of venous embolism, increased need for labor induction, and cesarean sections [ 301 ]. This is particularly important because of the higher rate of overweight and obesity in women of reproductive age.…”
Section: Adverse Perinatal Outcomes Related To Gdmmentioning
confidence: 99%